Large Ensemble Simulation for Investigating Predictability of Precursor Vortices of Typhoon Faxai in 2019 With a 14‐km Mesh Global Nonhydrostatic Atmospheric Model. Issue 3 (6th February 2023) - Yamada, Yohei; Miyakawa, Tomoki; Nakano, Masuo; Kodama, Chihiro; Wada, Akiyoshi; Nasuno, Tomoe; Chen, Ying‐Wen; Yamazaki, Akira; Yashiro, Hisashi; Satoh, Masaki
Abstract: Typhoon Faxai hit Japan in 2019 and severely damaged the Tokyo metropolitan area. To mitigate such damages, a good track forecast is necessary even before the typhoon formation. To investigate the predictability of the genesis and movement of a precursor vortex and its relationship with the synoptic‐scale flow, 100‐member ensemble simulations of Typhoon Faxai were performed using a 14‐km mesh global nonhydrostatic atmospheric model, which started from 16 different initial days (i.e., 1, 600 members in total). The results show that the model could predict an enhanced risk of a Faxai‐like vortex heading toward Japan 2 weeks before landfall, which was up to 70%. The reason for the enhancement was a rapid increase in the members reproducing a precursor vortex from 15 to 12 days before landfall in Japan. In addition, the upper‐tropospheric vortex played an essential role in the track simulation of Faxai. Plain Language Summary: Tropical cyclones severely damage coastal regions yearly. Typhoon Faxai hit Japan in 2019 and severely damaged buildings, power grids, and cell phone networks in the Tokyo metropolitan area. To mitigate such damages, better track forecast is necessary even from the timing before typhoon formation. A large ensemble member (1, 600‐member in total) and high‐resolution (14‐km) simulation was performed to investigate the genesis and movement of the precursor vortex of Faxai in 2019 and its relationship with the synoptic‐scale environmental flow using a global nonhydrostatic atmospheric model on the Supercomputer Fugaku. The results show the model could predict an enhanced risk of a Faxai‐like vortex heading toward Japan 2 weeks before landfall. A reason for the enhancement was a rapid increase in the members reproducing a precursor vortex from 15 to 12 days before landfall in Japan. In addition, the upper‐tropospheric vortex played an essential role in the movement of the Faxai‐like vortex. Key Points: A 1, 600‐member ensemble simulation in total for Typhoon Faxai (2019) was performed using a 14‐km mesh nonhydrostatic atmospheric model The model successfully predicts the risk of Faxai's landfall in Japan 2 weeks in advance Reproducibilities of the precursor vortex and upper‐tropospheric vortex yield good prediction of the formation and track of Faxai